THE ROLE OF BANKING CREDIT IN DEVELOPMENT LEADING SECTORS AT SOUTH SULAWESI PROVINCE - Abd. Rahman Razak (Jurnal Keuangan dan Perbankan, 2010)
This study aimed to measure how far the role of bank loans extended to supportthe development of leading sectors in South Sulawesi Province during the period 2003 - 2007as the period of observat ion. Data used were secondary data analyzed by using descript ivestat ist ical analysis tools and Locat ion Quot ient methods (LQ). To perform measurements, theresults of LQ calculat ion each economic leading sector of this region compared with thevalue of the share or the average percentage dist ribut ion of bank loans extended to everyeconomic sector. Results showed that there were 5 (f ive) sectors of the economy in SouthSulawesi Province that had values greater than 1 (one), so that the most valuable sector inthe economy of this region during the observat ion period, namely agriculture, mining andquarrying, elect ricity, gas and water supply, t ransport and communicat ions sector; and theservices sector. The role of bank credit in the development of leading sectors of this regionhad not been ef fect ive because there was st ill a fairly large gap between the value of its LQwinningeach of the sectors with the value of the average percentage of credit extended tothe leading sectors during the period of observat ion.